A novel silicate porous material and a preparation method and application thereof

A novel silicate porous material prepared by hydrothermal synthesis utilizes quaternary ammonium salt cations and linear primary amines as directing agents, overcoming the shortcomings of existing silicate porous materials in catalysis and sound absorption performance, and achieving high-efficiency catalytic performance and excellent low-frequency response value.

CN117945417BActive Publication Date: 2025-11-21SHANGHAI JIAOTONG UNIV +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410101808.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2025-11-21
Estimated Expiration
2044-01-24

AI Technical Summary

Technical Problem

Existing porous silicate materials have shortcomings in catalytic and sound absorption properties, making it difficult to meet the needs of various application systems, especially in the epoxidation reaction of cyclic olefin compounds and the acoustic performance of loudspeakers.

Method used

A novel porous silicate material with the chemical composition NnaSiOb was prepared by hydrothermal synthesis using quaternary ammonium salt cations and linear primary amines as structure directing agents. It has a specific X-ray diffraction structure and a pore size of 0.50-0.60 nm, and a specific surface area of ​​450-550 m2/g, making it suitable for catalytic and sound-absorbing materials.

Benefits of technology

It improves catalytic performance, especially conversion and selectivity in epoxidation reactions, and enhances the low-frequency response of the loudspeaker, resulting in higher conversion and product selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117945417B_ABST
    Figure CN117945417B_ABST
Patent Text Reader

Abstract

The application discloses a novel silicate porous material and a preparation method and application thereof. The application provides a novel microporous composite silicate material with an ordered crystal structure, which is characterized by a three-dimensional crystal structure formed by mutual connection of tetrahedral structure units of silicon oxide or other metal oxides, a pore size of 0.50-0.60 nm, a specific surface area of 450-550 m 2 / g, a uniform and ordered micropore channel structure, highly ordered channel arrangement and high crystallinity. The aluminiferous silicate can efficiently catalyze methanol to olefin and shows high propylene selectivity; the titanic silicate is a good olefin liquid phase epoxidation catalyst using hydrogen peroxide as an oxidant; the silicate porous material can be prepared into microparticles through post-forming, has good sound absorption capacity and can improve the acoustic performance of a loudspeaker.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of porous materials, and particularly relates to a novel silicate porous material and a preparation method and application thereof. BACKGROUND

[0002] Silicate porous materials are widely used in heterogeneous catalytic systems due to their regular pore structure, large specific surface area and good hydrothermal stability. In addition, they can be used as loudspeaker fillers to improve their acoustic performance due to their good sound absorption performance. Different silicate porous materials exhibit different performances in the above-mentioned application systems due to the differences between their pore structures. Although the International Zeolite Association (IZA) has published more than 250 silicate porous materials with different structures. However, the limited number of structures cannot meet the needs of numerous application systems.

[0003] Therefore, developing novel silicate porous materials with excellent performance has always been a hot topic in the research field. SUMMARY

[0004] The present application aims to provide a novel silicate porous material, which has significantly improved catalytic performance, higher conversion rate and product selectivity compared with traditional silicate materials, and has improved low-frequency response value compared with traditional sound-absorbing materials.

[0005] To achieve the above-mentioned purpose, the present application adopts the following technical solutions:

[0006] In a first aspect, the present application provides a silicate porous material, which mainly comprises: N n a SiO b ; wherein N is one or more than two of titanium, aluminum and germanium, a is the molar ratio of N to Si, which varies in the range of 1 / 500 to 1 / 10, b is the molar ratio of O to the total of Si and N, and n is the metal valence of N, then b=(a x n+4) ÷ 2.

[0007] In some embodiments, the silicate porous material has X-ray diffraction structure data (Cu-Ka, ) with the following diffraction peaks:

[0008]

[0009]

[0010] In the table, (a) is the relative intensity level of the diffraction peak in the powder X-ray diffraction pattern, W is a weak level diffraction peak; M is a medium level diffraction peak; S is a strong level diffraction peak; VS is the strongest level diffraction peak; the maximum value of the diffraction peak intensity is 100, the strongest level diffraction peak value is 60-100, the strong level diffraction peak value is 40-60, the medium level diffraction peak value is 20-40, and the weak level diffraction peak value is less than 20.

[0011] In a preferred embodiment, the pore size of the silicate porous material is 0.50-0.60 nm, the specific surface area is 450-550 m 2 / g.

[0012] In a second aspect, the present application provides a preparation method of the silicate porous material, which comprises a quaternary ammonium salt cation and a linear primary amine as a dual-structure directing agent, and the silicate porous material is prepared by a hydrothermal synthesis method. Specifically, the method comprises the following steps:

[0013] S1: mixing a silicon source calculated as SiO2, a metal source, a fluorine source, an organic structure directing agent I, an organic structure directing agent II and water according to a molar ratio of 1.0:0.002-0.1:0.02-0.5:0.2-1:0.2-1:1-50, stirring uniformly at room temperature for 1-24 hours to obtain a mixed gel; wherein the organic structure directing agent I and the organic structure directing agent II have the following structures:

[0014]

[0015] wherein: R1 is a linear alkyl group with 1-5 carbon atoms, preferably a linear alkyl group with 2-4 carbon atoms; R2 is a linear alkyl group with 2-4 carbon atoms, preferably a linear alkyl group with 3-4 carbon atoms;

[0016] S2: heating the mixed gel at a temperature of 120-200°C for 5-30 days, filtering, washing, drying and calcining the solid product to obtain the silicate porous material.

[0017] In some embodiments, the silicon source is selected from at least one of tetraethyl orthosilicate, fuming silica gel, silica sol and water glass.

[0018] In some embodiments, the metal source is one or two or more of a germanium source, an aluminum source and a titanium source, wherein the germanium source is selected from at least one of germanium dioxide, tetraalkoxy germanium and germanium nitrate; the aluminum source is selected from at least one of aluminum chloride, aluminum ethoxide, aluminum hydroxide, aluminum sulfate, alum, aluminum isopropyl alcohol, aluminum nitrate and aluminum butyl alcohol, and the titanium source is selected from at least one of titanium dioxide, n-butyl titanate and titanium nitrate.

[0019] In some embodiments, the fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride, potassium fluoride.

[0020] In some embodiments, in S1, the molar ratio of the silicon source to the metal source, the fluorine source, the organic structure-directing agent I, the organic structure-directing agent II, and water, calculated based on SiO2, is 1.0:0.02-0.1:0.2-0.4:0.2-0.4:0.2-0.4:10-30.

[0021] In some embodiments, in S1, the raw materials are stirred at room temperature for 8-16 hours.

[0022] In some embodiments, in S2, the mixed gel is reacted at a temperature of 130-170°C for 6-12 days.

[0023] In some embodiments, in S2, the calcination is performed at 550°C for 6 hours.

[0024] In some embodiments, the silicate porous material can be exchanged into a hydrogen-type silicate porous material by mixing the silicate porous material with an ammonium salt solution at a weight ratio of 1:10-100, exchanging at a temperature of 40-90°C for 1-24 hours, filtering, washing, drying, and calcining the solid product to obtain the hydrogen-type silicate porous material.

[0025] Further, the ammonium salt is selected from at least one of ammonium chloride, ammonium sulfate, and ammonium nitrate; and the ammonium salt solution is an aqueous solution of the ammonium salt, having a concentration of 0.2-3M, preferably 0.5-2.5M.

[0026] Further, the silicate porous material is exchanged with the ammonium salt solution at a temperature of 70-80°C for 5-8 hours.

[0027] In a third aspect, the present application provides use of the silicate porous material in catalyzing an epoxidation reaction of a cyclic olefin compound.

[0028] Further, the use comprises:

[0029] Step one: cyclic olefin compound, the silicate porous material, solvent, and hydrogen peroxide are sequentially added to a reaction kettle at a weight ratio of 1.0:0.02-0.10:2-20:0.20-2.0 to obtain a reaction liquid;

[0030] Step two: the reaction liquid is reacted at a temperature of 50-90°C for 30-120 minutes.

[0031] Step three: after the reaction is completed, the reaction liquid is taken out of the reaction kettle, cooled, and filtered to remove the silicate porous material, and the obtained product is a liquid of the epoxidation product.

[0032] Further, the cyclic olefin compound is a cyclic olefin compound with 5-10 carbon atoms, such as cyclohexene, cycloheptene, cyclooctene; the solvent is one of acetonitrile, propionitrile, acetone, butanone.

[0033] In the fourth aspect, the present application provides the application of the silicate porous material in catalyzing methanol to olefins.

[0034] Further, the application comprises:

[0035] Step one: 0.1-0.5g of the silicate porous material is loaded into a fixed bed reactor, and activated at 400℃ for 2 hours under nitrogen blowing;

[0036] Step two: methanol is introduced into the fixed bed at a flow rate of 30mL / min of nitrogen carrier gas, and the reaction temperature is 350℃, and the mass space velocity is 1-10h -1 ;

[0037] Step three: the reaction gas is collected to obtain the olefin product.

[0038] In the fifth aspect, the present application provides the application of the silicate porous material in making a loudspeaker.

[0039] Further, the application comprises:

[0040] Step one: the silicate porous material and an insoluble calcium source are added into a alginate solution, mixed uniformly, and then stirred to form droplets after adding paraffin oil and emulsifier; subsequently, acetic acid is added to gelate, and a gel is obtained;

[0041] Step two: the gel is aged, washed, dried, and calcined at high temperature to remove organic matter, and the silicate porous microspheres are obtained;

[0042] Step three: the silicate porous microspheres are filled into the loudspeaker as a filler.

[0043] In the above first to fifth aspects, the silicate porous material is a titanium-containing silicate porous material, an aluminum-containing silicate porous material, or a germanium-containing silicate porous material.

[0044] Technical effects

[0045] To develop a new type of silicate porous material and promote the development of the catalysis field and the loudspeaker acoustic field, the present application provides a new type of silicate porous material, a preparation method and application thereof, the structure and characteristics of which are that a microporous composite silicate material with a new three-dimensional ordered crystal structure is formed by connecting tetrahedral structural units of silicon oxide itself or other metal oxides, and the main chemical composition is: n a SiO bThe silicate porous material has a special diffraction characteristic peak and belongs to a new silicate structure which has not been reported.

[0046] The silicate porous material has a special diffraction characteristic peak and belongs to a new silicate structure which has not been reported. 2 / g of the silicate porous material prepared in the application is proved to have a uniform and ordered pore structure and good crystallinity through transmission electron microscope analysis.

[0047] The silicate porous material containing aluminum prepared in the application can efficiently catalyze methanol to olefins and show high propylene selectivity; the silicate porous material containing titanium prepared in the application is a good liquid phase selective catalyst for olefins with hydrogen peroxide as an oxidant; and the silicate porous material prepared in the application can be prepared into silicate microspheres through a molding method, has good sound absorption capacity and can improve the acoustic performance of a loudspeaker.

[0048] The silicate porous material prepared in the application has the characteristics of simple preparation method, wide source and high utilization rate of raw materials, novel structure and good crystallinity; compared with traditional catalysts, the conversion rate and product selectivity of the silicate porous material are obviously improved; and the low-frequency response value of the silicate porous material is more excellent than that of traditional sound-absorbing materials. BRIEF DESCRIPTION OF DRAWINGS

[0049] Figure 1 is a scanning electron microscope image of the silicate porous material prepared in Example 1 of the application;

[0050] Figure 2 is a transmission electron microscope image of the silicate porous material prepared in Example 1 of the application;

[0051] Figure 3 is an argon adsorption curve and pore size distribution diagram of the silicate porous material prepared in Example 1 of the application;

[0052] Figure 4 is a photo of the silicate porous microspheres prepared in Example 9 of the application. DETAILED DESCRIPTION

[0053] The following introduces a plurality of preferred embodiments of the application, so that the technical content of the application is clearer and easier to understand. The application can be embodied in many different forms of embodiments, and the protection scope of the application is not limited to the embodiments mentioned in the text.

[0054] In the application, the “silicate porous material” and the “new silicate porous material” can be used interchangeably.

[0055] Example 1

[0056] A preparation method of a titanium-containing silicate porous material, comprising the following steps:

[0057] S1: fumed silica, calculated as SiO2, is mixed with n-butyl titanate, ammonium fluoride, organic structure directing agent I, organic structure directing agent II and water in a molar ratio of 1.0:0.03:0.25:0.25:0.2:15, and stirred at room temperature for 8 hours until a clear transparent mixed gel is obtained, wherein the organic structure directing agent I and the organic structure directing agent II have the following structures:

[0058]

[0059] organic structure directing agent I organic structure directing agent II

[0060] In the organic structure directing agent I, R1 is a linear alkyl group with 3 carbon atoms; in the organic structure directing agent II, R2 is a linear alkyl group with 3 carbon atoms;

[0061] S2: the mixed gel is transferred to a high-pressure reaction kettle and heated at a temperature of 140°C for 8 days, and the solid product is filtered, washed, dried and calcined to obtain the titanium-containing silicate porous material.

[0062] The titanium-containing silicate porous material prepared in Example 1 is characterized by X-ray diffraction spectrum (XRD, Cu-Kα, ), and has good crystallinity and the following X-ray diffraction structure data shown in Table 1:

[0063] Table 1: X-ray diffraction structure data table of the new silicate porous material

[0064]

[0065]

[0066] In the table, (a) is the relative intensity level of the diffraction peak in the powder X-ray diffraction spectrum, W is a weak level diffraction peak, M is a medium level diffraction peak, S is a strong level diffraction peak, and VS is the strongest level diffraction peak. The maximum value of the diffraction peak intensity is 100, the strongest level diffraction peak value is 60-100, the strong level diffraction peak value is 40-60, the medium level diffraction peak value is 20-40, and the weak level diffraction peak value is less than 20.

[0067] It can be seen from Figure 1 that the titanium-containing new silicate porous material prepared in Example 1 is shown by scanning electron microscopy to be a blocky crystal morphology.

[0068] It can be seen from Figure 2It can be seen that the titanium-containing novel silicate porous material prepared in Example 1 has clear diffraction points and good crystallinity by transmission electron microscopy. The high-resolution image shows that it has uniform and ordered pores and highly ordered crystal structure.

[0069] By Figure 3 It can be seen that the titanium-containing novel silicate porous material prepared in Example 1 has microporous structure characteristics and high gas adsorption capacity by Ar adsorption experiment.

[0070] Example 2

[0071] A preparation method of an aluminum-containing silicate porous material, comprising the following steps:

[0072] S1: Tetraethyl orthosilicate calculated as SiO2, sodium metaaluminate, hydrofluoric acid, organic structure directing agent I, organic structure directing agent II and water are mixed in a molar ratio of 1.0:0.05:0.3:0.25:0.3:20, and stirred at room temperature for 12 hours until a clear and transparent mixed gel is obtained; wherein the structures of the organic structure directing agent I and the organic structure directing agent II are as follows:

[0073]

[0074] In the organic structure directing agent I, R1 is a linear alkyl group with 2 carbon atoms; in the organic structure directing agent II, R2 is a linear alkyl group with 3 carbon atoms;

[0075] S2: The above mixed gel is transferred to a high-pressure reaction kettle and heated at a temperature of 160°C for 10 days, and the solid product is filtered, washed, dried and calcined to obtain an aluminum-containing novel silicate porous material.

[0076] S3: The aluminum-containing novel silicate porous material is mixed with a 2M ammonium chloride solution at a weight ratio of 1:30, and exchanged at a temperature of 80°C for 2 hours, and the solid product is filtered, washed, dried and calcined to obtain a hydrogen-type aluminum-containing novel silicate porous material.

[0077] Example 3

[0078] A preparation method of an aluminum-containing silicate porous material, comprising the following steps:

[0079] S1: A silica sol calculated as SiO2, aluminum sulfate, potassium fluoride, organic structure directing agent I, organic structure directing agent II and water are mixed in a molar ratio of 1.0:0.07:0.35:0.2:0.4:30, and stirred at room temperature for 16 hours until a clear and transparent mixed gel is obtained; wherein the structures of the organic structure directing agent I and the organic structure directing agent II are as follows:

[0080]

[0081] In the organic structure-directing agent I, R1 is a linear alkyl group with 4 carbon atoms; in the organic structure-directing agent II, R2 is a linear alkyl group with 4 carbon atoms;

[0082] S2: The mixed gel is transferred to a high-pressure reactor and heated at 170°C for 11 days. The solid product is filtered, washed, dried, and calcined to obtain an aluminum-containing novel silicate porous material;

[0083] In Examples 4-6, the titanium-containing novel silicate porous material prepared in Example 1 is used as a catalyst for the epoxidation of cyclic olefins, and its application is further described:

[0084] Example 4

[0085] Step one: cyclohexene, titanium-containing novel silicate porous material prepared in Example 1, acetone, and hydrogen peroxide are sequentially added to the reactor, and mixed in a weight ratio of 1.0:0.06:12:1.0.

[0086] Step two: the reactor is placed in a 70°C temperature environment and heated and stirred for 60 minutes.

[0087] Step three: after the reaction is completed, the reaction liquid is removed from the reactor, cooled, and filtered to remove the catalyst silicate porous material, resulting in a liquid product of epoxy cyclohexane.

[0088] TS-1 titanium silicalite is used as a control, and TS-1 titanium silicalite is synthesized according to the method in the literature (Catal. Today, 2022, 405, 193-202), SiO2 / TiO2=30, and the reaction conditions are the same as the above steps one to three.

[0089] The above reaction liquid is analyzed by gas chromatography (Shimadzu-14B, FID), and the catalytic performance is shown in Table 2.

[0090] Table 2: Comparison of catalytic performance of titanium-containing novel silicate porous material and TS-1 titanium silicalite

[0091]

[0092] It can be seen that when the titanium-containing novel silicate porous material prepared in Example 1 is used as a catalyst, the conversion rate of cyclohexene is 23%, and the selectivity of epoxy cyclohexane is 98.9%, which is much higher than that of TS-1 titanium silicalite in the epoxidation reaction of cyclohexene.

[0093] Example 5

[0094] Step one: cycloheptene, the new titanium-containing silicate porous material prepared in Example 1, acetonitrile and hydrogen peroxide were sequentially added into the reaction kettle, and mixed according to the weight ratio of 1.0:0.07:15:1.1.

[0095] Step two: the reaction kettle was placed at a temperature of 80°C, heated and stirred, and reacted for 120 minutes.

[0096] Step three: after the reaction was completed, the reaction liquid was taken out of the reaction kettle, cooled, and the catalyst silicate porous material was removed by filtration, and the product was a liquid of cyclohexene oxide.

[0097] TS-1 titanium silicalite was used as a control, and TS-1 titanium silicalite was synthesized according to the method in the literature (Catal. Today, 2022, 405, 193-202), SiO2 / TiO2=30, and the reaction conditions were the same as the above steps one to three.

[0098] The above reaction liquid was analyzed by gas chromatography (Shimadzu-14B, FID), and the catalytic performance was shown in Table 3.

[0099] Table 3: Comparison of catalytic performance of new titanium-containing silicate and TS-1 titanium silicalite

[0100]

[0101] It can be seen that when the new titanium-containing silicate porous material prepared in Example 1 is used as a catalyst, the conversion rate of cycloheptene is 19%, and the selectivity of cyclohexene oxide is 99.6%, which is much higher than that of TS-1 titanium silicalite in the epoxidation reaction of cycloheptene.

[0102] Example 6

[0103] Step one: cyclooctene, the new titanium-containing silicate porous material prepared in Example 1, acetonitrile and hydrogen peroxide were sequentially added into the reaction kettle, and mixed according to the weight ratio of 1.0:0.10:12:1.2.

[0104] Step two: the reaction kettle was placed at a temperature of 70°C, heated and stirred, and reacted for 100 minutes.

[0105] Step three: after the reaction was completed, the reaction liquid was taken out of the reaction kettle, cooled, and the catalyst silicate porous material was removed by filtration, and the product was a liquid of cyclohexene oxide.

[0106] TS-1 titanium silicalite was used as a control, and TS-1 titanium silicalite was synthesized according to the method in the literature (Catal. Today, 2022, 405, 193-202), SiO2 / TiO2=30, and the reaction conditions were the same as the above steps one to three.

[0107] The reaction solution was analyzed by gas chromatography (Shimadzu-14B, FID), and the catalytic performance is shown in Table 4.

[0108] Table 4: Comparison of catalytic performance of new titanium-containing silicate porous material and TS-1 titanium silicate molecular sieve

[0109]

[0110] It can be seen that when the new titanium-containing silicate porous material prepared in Example 1 is used as a catalyst, the conversion rate of cyclooctene is 14%, and the selectivity of cyclooctene oxide is 99.8%, which is much higher than that of TS-1 titanium silicate molecular sieve in the cyclooctene epoxidation reaction.

[0111] In Examples 7 and 8, the new aluminum-containing silicate porous material prepared in Example 2 is used as a catalyst for the preparation of olefins from methanol, and its application is further described:

[0112] Example 7

[0113] Step 1: Put the new aluminum-containing silicate porous material prepared in Example 2 into a quartz reaction tube, activate it in nitrogen at 400°C for 2h, then reduce the temperature of the reaction tube to 350°C.

[0114] Step 2: Introduce methanol into the fixed bed at a nitrogen carrier gas flow rate of 30mL / min, the reaction temperature is 350°C, and the mass space velocity is 4h -1 ; the mass of the catalyst used is 0.2g.

[0115] Step 3: The reaction gas is introduced into the gas chromatograph for online analysis to obtain the conversion rate of methanol and the selectivity of olefins.

[0116] ZSM-5 silico-alumina molecular sieve was used as a control catalyst, ZSM-5 silico-alumina molecular sieve was synthesized according to the literature (ACS Catal., 2019, 10, 1185-1194), SiO2 / Al2O3=15, and the reaction conditions were the same as steps 1-3 above.

[0117] The catalytic performance is shown in Table 5 by gas chromatography (Shimadzu-14B, FID) analysis.

[0118] Table 5: Comparison of catalytic performance of new aluminum-containing silicate porous material and ZSM-5 silico-alumina molecular sieve

[0119]

[0120] As can be seen, when the new aluminiferous silicate porous material prepared in Example 2 is used as a catalyst, the methanol conversion rate is 99.8%, and the selectivity of propylene is 55%, which is much higher than that of ZSM-5 silico-alumina molecular sieve in the methanol-to-olefins reaction.

[0121] Example 8

[0122] Step one: the new aluminiferous silicate porous material prepared in Example 2 was placed in a quartz reaction tube and activated in nitrogen at 400℃ for 2h, and then the temperature of the reaction tube was reduced to 350℃.

[0123] Step two: methanol was introduced into the fixed bed in a nitrogen carrier gas at a flow rate of 30mL / min, the reaction temperature was 350℃, and the mass space velocity was 6h -1 ; the mass of the catalyst used was 0.5g.

[0124] Step three: the reaction gas was introduced into a gas chromatograph for online analysis to obtain the methanol conversion rate and the selectivity of olefins.

[0125] ZSM-5 silico-alumina molecular sieve was used as a control catalyst, and the ZSM-5 silico-alumina molecular sieve was synthesized according to the method in the literature (ACS Catal., 2019, 10, 1185-1194), SiO2 / Al2O3=15, and the reaction conditions were the same as steps one to three above.

[0126] The catalytic performance was analyzed by gas chromatography (Shimadzu-14B, FID), and the results are shown in Table 6.

[0127] The catalytic performance of the new aluminiferous silicate porous material and ZSM-5 molecular sieve was compared, and the results are shown in Table 6.

[0128] Table 6: Comparison of catalytic performance of new aluminiferous silicate porous material and ZSM-5 silico-alumina molecular sieve

[0129]

[0130] As can be seen, when the new aluminiferous silicate porous material prepared in Example 2 is used as a catalyst, the methanol conversion rate is 99.3%, and the selectivity of propylene is 50%, which is much higher than that of ZSM-5 silico-alumina molecular sieve in the methanol-to-olefins reaction.

[0131] In Examples 9-11, the new silicate porous material prepared in Example 3 was used as a speaker filler to improve the acoustic performance of the speaker, and the application thereof was further described:

[0132] Example 9

[0133] Step one: The new silicate porous material (initially in potassium form) prepared in Example 3 and calcium carbonate were added to an alginate solution and mixed uniformly. After adding paraffin oil and emulsifier, the mixture was stirred to form droplets. Subsequently, acetic acid was added to cause gelation. In this process, the calcium carbonate, silicate porous material, sodium alginate and water were mixed in a weight ratio of 1:20:1.1:66.7, the emulsifier and paraffin oil were mixed in a volume ratio of 1:30, the amount of acetic acid added was 2.5 mL, the stirring speed was 550 revolutions per minute, and the stirring lasted for 10 minutes.

[0134] Step two: The mixture was allowed to stand and age for 24 hours, washed with ethanol and water, dried, and calcined at high temperature to remove organic matter, thereby obtaining the new silicate porous microspheres.

[0135] Step three: The prepared new silicate porous microspheres were filled into the rear cavity of a loudspeaker (1.0 cc), and the rear cavity was closed. Subsequently, the micro-loudspeaker and the acoustic test platform were connected, the input loudspeaker electrical signal parameters were set, and the acoustic performance was tested (Table 7).

[0136] Referring to the accompanying Figure 4 The prepared new silicate porous microspheres had a smooth surface and uniform particles.

[0137] Example 10

[0138] Step one: The new silicate porous material (in potassium form) prepared in Example 3 was mixed with a 2M sodium chloride solution in a weight ratio of 1:30 and exchanged at a temperature of 80°C for 3 hours. The solid product was filtered, washed, dried, and calcined to obtain a sodium-type silicate porous material. Then, the sodium-type silicate porous material and calcium carbonate were added to an alginate solution and mixed uniformly. After adding paraffin oil and emulsifier, the mixture was stirred to form droplets. Subsequently, acetic acid was added to cause gelation. In this process, the calcium carbonate, silicate porous material, sodium alginate and water were mixed in a weight ratio of 1:20:1.1:66.7, the emulsifier and paraffin oil were mixed in a volume ratio of 1:30, the amount of acetic acid added was 2.5 mL, the stirring speed was 550 revolutions per minute, and the stirring lasted for 10 minutes.

[0139] Step two: The mixture was allowed to stand and age for 24 hours, washed with ethanol and water, dried, and calcined at high temperature to remove organic matter, thereby obtaining the new silicate porous microspheres.

[0140] Step three: The prepared new silicate porous microspheres were filled into the rear cavity of a loudspeaker (1.0 cc), and the rear cavity was closed. Subsequently, the micro-loudspeaker and the acoustic test platform were connected, the input loudspeaker electrical signal parameters were set, and the low-frequency acoustic performance was tested (Table 7).

[0141] Example 11

[0142] Step one: the new silicate porous material (potassium type) prepared in Example 3 was mixed with 3M ammonium chloride solution at a weight ratio of 1:30, and exchanged at 80℃ for 3 hours. The solid product was filtered, washed, dried and calcined to obtain a hydrogen type silicate porous material. Then, the hydrogen type silicate porous material and calcium carbonate were added to an alginate solution, mixed uniformly, and stirred to form droplets after adding paraffin oil and emulsifier. Subsequently, gelation was performed by adding acetic acid. The weight ratio of calcium carbonate, silicate porous material, sodium alginate and water was 1:20:1.1:66.7, the volume ratio of emulsifier and paraffin oil was 1:30, the amount of acetic acid added was 2.5mL, the stirring speed was 550rpm, and the stirring time was 10 minutes.

[0143] Step two: aging for 24 hours, washing with ethanol and water, drying, and high-temperature calcination to remove organic matter to obtain the new silicate porous microspheres.

[0144] Step three: the prepared new silicate porous microspheres were filled into the rear cavity of a loudspeaker (1.0cc), and the rear cavity was closed. Subsequently, the micro-loudspeaker and the acoustic test platform were connected, the input loudspeaker electrical signal parameters were set, and the low-frequency acoustic performance was tested (Table 7).

[0145] Table 7: Resonance frequency difference before and after adding new silicate porous microspheres in the rear cavity of a loudspeaker.

[0146] Number F (Hz) ΔF (Hz) Blank 679.231 0.000 Example 9 495.722 183.509 Example 10 491.306 187.925 Example 11 511.432 167.799

[0147] According to Table 7, it can be concluded that after filling the new silicate porous microspheres of Examples 9-11 in the rear cavity of a loudspeaker, the resonance frequency change △F (Hz) of the loudspeaker is greatly reduced.

[0148] The protection scope of the present application is not limited to the above examples, and any changes and advantages that can be thought of by those skilled in the art without departing from the spirit and scope of the present application are included in the present application, and are protected by the appended claims.

Claims

1. A silicate porous material having a primary chemical composition of: N n a SiO b ; wherein, N is one or more than two of titanium, aluminum, germanium, a is the molar ratio of N to Si, which varies in the range of 1 / 500 to 1 / 10; b is the molar ratio of O to the sum of Si and N, n is the metal valence of N, then b = (a x n + 4) ÷ 2; the silicate porous material has the X-ray diffraction structure data as shown in the following diffraction peak, Cu-Kα, λ = 1.5406 Å: In the table: a is the relative intensity level of the diffraction peak in the powder X-ray diffraction pattern, W is the weak level diffraction peak; M is the medium level diffraction peak; S is the strong level diffraction peak; VS is the strongest level diffraction peak; the maximum value of the diffraction peak intensity is 100, the strongest level diffraction peak value is 60-100, the strong level diffraction peak value is 40-60, the medium level diffraction peak value is 20-40, and the weak level diffraction peak value is less than 20.

2. The silicate porous material of claim 1, wherein, The silicate porous material has a pore size of 0.50-0.60 nm, a specific surface area of 450-550 m 2 / g.

3. The preparation method of the silicate porous material of claim 1 or 2, comprising the following steps: S1 : mixing the silicon source, the metal source, the fluorine source, the organic structure-directing agent I, the organic structure-directing agent II and water in a molar ratio of 1.0:0.002-0.1:0.02-0.5:0.2-1:0.2-1:1-50 in terms of SiO2, stirring at room temperature for 1-24 hours to mix uniformly to obtain a mixed gel; wherein, The organic structure directing agent I and the organic structure directing agent II have the following structures: The organic structure directing agent I and the organic structure directing agent II have the following structures: Wherein: R1 is a linear alkyl group with 1-5 carbon atoms; R2 is a linear alkyl group with 2-4 carbon atoms; S2: heating the mixed gel at a temperature of 120-200°C for 5-30 days, filtering, washing, drying and calcining the solid product to obtain the silicate porous material.

4. The method of claim 3, wherein, The metal source is one or more than two of a germanium source, an aluminum source and a titanium source.

5. The method of claim 3, wherein, The silicate porous material is exchanged into a hydrogen-type silicate porous material, comprising mixing the silicate porous material with an ammonium salt solution at a weight ratio of 1:10-100, exchanging at a temperature of 40-90°C for 1-24 hours, filtering, washing, drying and calcining the solid product to obtain a hydrogen-type silicate porous material; the ammonium salt is at least one of ammonium chloride, ammonium sulfate and ammonium nitrate; the ammonium salt solution is an aqueous solution of the ammonium salt, and the concentration is 0.2-3 M.

6. The application of the silicate porous material of claim 1 or 2 in catalyzing the epoxidation reaction of a cyclic olefin compound.

7. Use according to claim 6, wherein, The cyclic olefin compound is a cyclic olefin compound with 5-10 carbon atoms.

8. The application of the silicate porous material of claim 1 or 2 in catalyzing the methanol-to-olefin reaction.

9. The application of the silicate porous material of claim 1 or 2 in making a loudspeaker.

Citation Information

Patent Citations

  • Preparation method of titanium-silicon molecular sieve and application

    CN103818924A

  • Crystalline aluminium silicates and gallium silicates, process for their preparation and their use as catalysts in the preparation of lower olefins

    DE3237389A1